A relação da divulgação das práticas ESG com o valor de mercado das empresas brasileiras de capital aberto - Martins, Mayra (2022)
The ESG term, symbolizing the concern of companies with environmental, social and corporate governance issues, is the newest attention of the capital market. Thus, this study aimed to investigate the association between the disclosure of the practice of sustainability ESG factors by publicly traded Brazilian companies with their market values, checking the ESG (total) and also the factors separately (environmental, social and governance) as specific objectives. The research sample had data from 106 B3 companies, between 2012 and 2020. As a methodology, the Bloomberg databases were used for ESG data and Refinitiv Thomson Reuters for the other variables. The variables for market value were Tobin's Q and market-to-book, to create greater robustness and, as a statistical technique, panel data regression. As a result, it was found that the ESG factors were not significant in relation to market value, with the exception of variable S (social), which showed a significant and positive association with Tobin's Q metric. Thus, it can be considered that the disclosure of the social factor is the only one, so far, that stands out as relevant for participants in the Brazilian capital market.